Membrane Systems and Petri Net Synthesis - Marta Pietkiewicz-Koutny; Grzegorz Rozenberg; Jetty Kleijn; Maciej Koutny (Electronic Proceedings in Theoretical Computer Science, 2012)
Automated synthesis from behavioural specifications is an attractive and powerful way of constructing concurrent systems. Here we focus on the problem of synthesising a membrane system from a behavioural specification given in the form of a transition system which specifies the desired state space of the system to be constructed. We demonstrate how a Petri net solution to this problem, based on the notion of region of a transition system, yields a method of automated synthesis of membrane systems from state spaces.